Teaching argumentative writing to teachers and students: effects of professional development. Issue 2 (15th March 2018) - Howell, Emily; Hunt-Barron, Sarah; Kaminski, Rebecca; Sanders, Rachel
Abstract: This multiple-case study design with embedded units of analysis examined a two-year professional development (PD) program in which two rural districts received at least 90 hours of PD. This PD was provided through an Investing in Innovation (i3) grant that the United States Department of Education awarded to the National Writing Project. Two of the three districts receiving PD served as cases for this study, and researchers interviewed, surveyed and observed both a high-adopting teacher and a low-adopting teacher from each case. The data from these high-adopting and low-adopting teachers serve as the embedded units of analysis. The researchers found that teachers did adopt and adapt the PD, as seen in their increased time spent on writing and survey data indicating their adoption of strategy instruction. Student outcomes also showed a positive impact because student writing sample scores increased after the PD. The findings from both of the overall cases and the embedded units led the researchers to five discussion points regarding the adoption of PD.